PENERAPAN DESAIN PEMBELAJARAN DALAM MENINGKATKAN MUTU PENDIDIKAN - Mardyawati Mardyawati (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Improving the quality of education in Indonesia is a national education goal. But this has become an ideal goal because various literature and research results present the low quality of education in Indonesia. The causes of the low quality of education include issues of effectiveness, efficiency and standardization of teaching, this is still a problem in the field of education in Indonesia in general. In addition to a centralistic curriculum, making portraits of education increasingly opaque and less creative of educators is the main problem. This is a challenge for educators at every level and level of education in Indonesia. It is understood that learning is a process, way, action to make people or living things learn so that the need for learning design. With the application of learning design can make it easier for educators to present and measure the success of learning.